Effect of Glycyrrhiza on the Diuretic Function of Euphorbia kansui: An Ascites Mouse Model. (9th May 2016) - Lin, Ya; Zhang, Yanqiong; Shang, Erxin; Lai, Wenfang; Zhu, Hongwei; Fang, Yuhua; Qin, Qingxia; Zhao, Haiyu; Lin, Na
Abstract : We investigated the therapeutic role of the herbal combination Euphorbia kansui (GS) and Glycyrrhiza (GC) in ascites during hepatocellular carcinoma (HCC). The AVPR2 and AQP2 expression in kidney tissues of ascites mice in different groups was determined by immunohistochemistry, Western blot, and real-time PCR analyses. When the dose of GS was less than 0.70 g/kg at a ratio of GC : GS not exceeding 0.4 : 1, the combination of GS and GC exhibited synergistic effects on HCC ascites and significantly elevated the expression levels of AVPR2 and AQP2 (allP < 0.05 ). On the contrary, when GS ≥ 0.93 g/kg and GC ≥ 1.03 g/kg with the GC-to-GS ratio exceeding 1.11 : 1, the combination of GS and GC displayed antagonistic effects on HCC ascites and dramatically reduced the expression levels of AVPR2 and AQP2 (allP < 0.05 ). Furthermore, the administration of herbal pair GS and GC at different ratios did not exacerbate the pathological changes in liver and kidney tissues of HCC ascites mice. The different combinations of GS and GC exerted synergistic or antagonistic effects on HCC ascites, partially by regulating the expression of AVPR2 and AQP2.